New venture creation entrepreneurship for the 21st century - Timmons, Jeffry A. (McGraw-Hill/Irwin, 2009)
The entrepreneurial mind for an entrepreneurial world; The opportunity; The founder and team; Financing entrepreneurial ventures; Startup and beyond.